Determination of Zone Degradation for Sulfide (S2-) and Ammonia (NH3) in the Leachate from TPA Pakusari (Pakusari Landfill), Jember, Using Spectrophotometric Method - Wijayanti, Chatarina; Siswoyo, Siswoyo; Mintadi, Mukh.; Maulidah Muflihah, Yeni (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2022)
Leachate as a result from waste decomposition at landfills potentially contain toxic materials, including metals and organic matters. This leachate produces several environmental issues, including groundwater and surface water resources contamination. The landfill leachate can penetrate to the soil, blend with the soil water, flow to the soil surface, and then disembogue at the river channel. The contamination processes will vary depending on the contaminating substances and their degradation zone. Our study focused on analyzing sulfide and ammonia in the leachate. The sulfide and ammonia degradation zone have been determined by measuring the concentration of sulfide and ammonia using Spectro quant NOVA 60. The degradation zone determination ranged from the distances: 0 m, 50 m, 100 m, 150 m, and 200 m direct to the north, south, and west, and at distances of 0 m and 400 m in the east direction. The range of degradation zone based on the concentration of sulfide, ammonia, and DO (dissolved oxygen) was in a range between 150 m and 200 m from the leachate water reservoir located at TPA Pakusari (Pakusari Landfill) Jember.